(untitled) (Fiep Bulletin - online, 2015)
From 12th to 16th October 1966, the city of o porto was the seat of an important international meeting organized by the national foundation for joy in work (FNAT) which took place with the cooperation of the FIEP and PSSM and the patronage of the ICSPSM the colloquium was held in the stock-exchange palace and gathered together about 120 participants coming from Belgium, brazil, Spain USA France Great Britain, Portugal, Sweden and Czechoslovakia.